Guía de identificación de fauna silvestre, para las autoridades ambientales de Amazonas, San Martín, Loreto y Ucayali. A review and notes about its importance - Serrano-Villavicencio, José Eduardo (2018)
The Guía de identificación de fauna silvestre para las autoridades ambientales de Amazonas, San Martín, Loreto y Ucayali (ISBN: 978-612-4261-24-4) was published in order to provide a tool for authorities related to the fight against wildlife trafficking and trade.This guide represents an important tool, so the information transmitted should be as current and reliable as possible. However, after reviewing the section dedicated to mammals, we identified several errors that could generate confusion and be counterproductive in the fight against wildlife trafficking. Although we emphasize the importance of this work, we suggest caution in the preparation of documents such as this guide in order to maximize its usefulness for the authorities that fight wildlife trafficking in our territory.